Generation of a galactic chronology with impact ages and spiral arm tangents - Michael Gillman; Rui Zhang (Scientific Reports, 2024)
Abstract Resolving the role of galactic processes in Solar System/Earth events necessitates a robust temporal model. However, astrophysical theory diverges with models varying from long-lasting spiral density waves with uniform pattern speeds and arm structures to others with fleeting and unpredictable features. Here, we address those issues with (1) an analysis of patterns of impact periodicity over periods of 10 to 250 million years (Myr) using circular statistics and (2), an independent logarithmic spiral arm model fitted to arm tangents of 870 micron dust. Comparison of the impact periodicity results with the best-fit spiral arm model suggests a galactic period of 660 Myr, i.e. 165 Myr to pass from one arm to the next in a four spiral arm model, with the most recent arm passage around 52 million years ago (Ma). The oldest impact ages imply that the emerging galactic chronology model is robust for at least the last 2 Gyr. The arm-passing time is consistent with spectral analyses of zircons across 3 Gyrs. Overall, the model provides a temporal framework against which to test hypotheses of galactic mechanisms for global events such as mass extinctions and superchrons.